TRAINING IN ACCOUNTING, MANAGEMENT IN MSMES IN DUSUN BEGAWAN, DESA PANDANSARI LOR, KABUPATEN MALANG - Dwi Ekasari Harmadji; FX Hevie Dwi Novianto; A. Margaretha Andreany Patty Corrua (JURNAL PENGABDIAN KEPADA MASYARAKAT, 2022)
The Community Service Program through the Thematic Community Service Program aims to empower the community with the application of science and technology, as well as empower and improve the local economy of the community through management accounting for Micro, Small and Medium Enterprises (MSMEs) processing chips (agricultural products) in Begawan Hamlet, Pandansari Lor Village, Jabung District, Malang Regency. This is supported by the results from agriculture in the form of tubers and bananas which are abundant and used as community livelihoods. Chips SMEs become a reference for the application of management accounting for field supervisors and KKN students. SMEs processing cassava and banana chips there still need improvement in terms of management accounting and marketing as well as the processing process. This is of course able to increase the income of the community of MSME actors. Empowerment of management accounting strengthening is carried out through training and mentoring methods to provide solutions to problems faced by MSMEs. This training and mentoring has been carried out by Field Supervisors together with thematic KKN students consisting of accounting, management and civil engineering disciplines. The real implication of this thematic KKN activity is the realization of effective and efficient MSME management accounting, so as to increase the income of the MSME community in Dusun Begawan, Pandansari Lor Village, Malang Regency.